IMPLEMENTASI ALGORITMA FUZZY LOGIC PADA ROBOT ARM DENGAN MEMANFAATKAN ACCELEROMETER SMARTPHONE ANDROID - Nanda Tommy Wirawan; Retno Devita (Universitas Negeri Padang, 2017)
Now the development of smart phone technology has evolved rapid, especially Smartphone Android. Where multiple sensors embedded in a mobile phone, primarily an accelerometer sensor support be used of smartphone phone. Accelerometer is used to measure the acceleration reviews Angle X, Y and Z smartphone. So that the sensor is used to review the Movement Robot Arm matching is done with corner acceleration motion X, Y and Z smartphone Method on the system is backed with Fuzzy Logic the which serves to Determine the movement of the robot arm that is sent to the microcontroller. Arm robot system is processed using Matlab 6.1 and using the Software Arduino, and then implanted into the microcontroller, so that the robot goes According movement. Keywords : Android, Accelerometer, Robot Arm, Fuzzy Logic